Associations Between Sex Hormone Levels and Autistic Traits in Infertile Patients With Polycystic Ovary Syndrome and Their Offspring - Jiang, Lijie; Tian, Li; Yuan, Jiajia; Xu, Xinjie; Qu, Fan; Zhang, Rong; Wang, Jianliu (Frontiers in Endocrinology, 2022)
Objectives: 1) To explore the associations between autistic traits and related sex hormone changes in patients with Polycystic Ovary Syndrome (PCOS); 2) To explore the influence of PCOS parental autistic traits and related sex hormone changes on offspring autistic traits. Method: This is a case-control study that recruited two groups: polycystic ovarian syndrome as the test group and fallopian tube factors subjects as the control group. Both cohorts were undergoing infertility treatment in the Productive Medicine Center, Peking University People’s Hospital. Two types of questionnaires were completed by patients: 1. The autism-spectrum quotient (AQ) 2. Repetitive behavior scale-revised (RBS-r). Levels of sex hormone in serum were measured in patients. The correlations between levels of these biochemical factors and scores of the autistic traits were analyzed. Recently, these patients were contacted by telephone and asked to fill out a questionnaire online. Results: the patients in the PCOS group had significantly higher scores of AQ compared to those in the control group. Levels of luteinizing hormone and testosterone were also higher in the PCOS group. No significant differences were found between the two groups in scores of RBS-r levels, follicle-stimulating hormone, estradiol or progesterone. In the PCOS group, there were significantly positive correlations between the AQ scores and the luteinizing hormone concentration, as well as, between scores of RBS-r and testosterone. Moreover, there was a significantly negative correlation between the level of progesterone and the RBS-r score. According to the follow-up data, the AQ scores of offspring were positively correlated with the RBS-r scores of their mothers. The ABC scores of offspring were positively correlated with the RBS-r scores or the childbearing age of their mothers. Conclusion: Compared with the control group, PCOS patients had more autistic traits. The autistic traits in PCOS patients might be related to the elevation in testosterone concentration and luteinizing hormone levels, and the autistic traits in PCOS patients might be related to the decline in progesterone levels. Moreover, the autistic traits in the offspring of PCOS patients might be related to the parental high delivery age and high tendency to autism traits.